Prevalence of Urinary Incontinence in Females Performing High-Impact Exercises - Hagovska, Magdaléna; Ján, Švihra; Buková, Alena; Horbacz, Agáta; Dračková, Dana; Švihrová, Viera; Kraus, Lenka (International Journal of Sports Medicine, 2017)
The aim of this cross-sectional study was to monitor the prevalence of symptoms of stress (SUI) and mixed urinary incontinence (MUI) in sportswomen performing high-impact exercises. A further objective was to compare the symptoms of urinary incontinence (UI) and quality of life in sportswomen. We used the International Consultation on Incontinence Questionnaire (ICIQ-SF), the Overactive Bladder Questionnaire (OAB-q), the Urinary Incontinence Quality of Life Scale (I-QOL) and the International Physical Activity Questionnaire (IPAQ), short version. The group consisted of 503 sportswomen with a mean age of 21.1±3.6. The response rate was 71.15%. ICIQ-SF results confirmed mild difficulties with urine leakage in 72 (14.3%) sportswomen. Urinary leakage was not noted in 431 (85.7%) sportswomen. The OAB-q and I-QOL showed a significant difference, with pronounced symptoms of UUI and worse QOL in the group of sportswomen with urine leakage (p<0.000). The I-QOL recorded significantly worse parameters in the group of sportswomen with urine leakage (p<0.000). Prevalence of SUI was found in 68 (13.52%), and MUI was found in 4 (0.80%) sportswomen. Every seventh sportswoman (14.3%) in the study group had reported problems with UI when practising high-impact sporting activities, with a negative impact on QOL.
Keywords: prevalence; urinary incontinence; high-impact exercises